The model suburb : the Savage Crescent State Housing Precinct, Palmerston North : a research exercise presented in partial fulfilment of the requirement for the Bachelor of Arts with Honours in History at Massey University - Bragg, Alaric (Massey University, 2004)
A significant aspect of the policy of the First Labour Government of New Zealand upon coming to power in 1935 was housing. Housing was always an issue for governments and political parties during the early half of the Twentieth .ctfntury in New Zealand, but it was only after the Depression of the 1930s that it was brought to the fore. In fact, the history of government housing schemes in New Zealand dates back to the mid- l 890s, when health reformers argued that slum dwellings would become a feature of towns and cities in the country unless more adequate housing was built to replace them. In 1900, they successfully pressed for inclusion of municipal housing schemes in the Municipal Corporations Act of that year, which permitted local bodies to both buy land and construct workers dwellings on it, and to buy existing houses for workers. 1 The act would become the basis of the ideals that shaped the planning, construction and promotion of government housing schemes in years to come. [From Introduction.]